Uterine Involution On The First Day In Postpartum Mothers With Normal Delivery - Puji Astutik; Deva Tiananda Putri (Master of Public Health Program Universitas STRADA Indonesia, 2026)
After delivery, the uterus gradually shrinks back to its original shape, a process known as uterine involution. One indicator of this involution process is a decrease in the uterine fundus (FFU). The uterine fundus descends 1-2 cm every 24 hours. On the first day postpartum, the FFU drops 1 cm below the umbilicus. The purpose of this study was to describe uterine involution on the first day in postpartum women with normal deliveries in the Delima Ward of Kertosono Hospital. This study used a descriptive design and was conducted from January 13, 2025, to February 13, 2025, and April 9, 2025, to May 9, 2025, in the Delima Ward of Kertosono Hospital. The population consisted of 29 postpartum women with normal deliveries. A sample of 25 respondents was selected using an accidental sampling technique. The research variable was uterine involution on the first day. Data were collected by measuring the FFU. Based on the research results, the majority of 25 respondents (14 respondents (56%) experienced uterine involution on the first day at 2 cm below the umbilical cord, and nearly half (11 respondents (44%) experienced uterine involution on the first day at 1 cm below the umbilical cord. The results of the research showed that the majority of uterine involution on the first day was 2 cm below the umbilical cord. This can be influenced by early mobilization (toileting), early breastfeeding (IMD), good nutritional status, age above 20-30 years, and parity of the mother who has had more than one postpartum period. Early mobilization and early breastfeeding (IMD) are the most important factors in accelerating uterine involution because they increase blood flow and help release the hormone oxytocin, which can stimulate uterine contractions.